Development and application of a lightweight five-axis parallel machining robot - Zenghui XIE; Bin MEI; Weiyao BI; Fugui XIE; Xin-Jun LIU (物联网学报)
In the fields of national defense, aerospace, and energy, there exist plenty of complex surface core parts, for example, the aircraft structural components and turbine blades.These parts usually have the machining requirements of large material removal rate, high dimensional accuracy and high surface quality.The traditional five-axis serial machine centers face two problems in the machining process: (1) the tool will automatically rotate when it passes through the pole posture; (2)the driving axes’dynamic response does not match.It was tried to solve these problems from the view of machining equipments’ configuration.By making fully use of the advantages of parallel robots in compact structure, high stiffness, kinematic flexibility and dynamic response, a lightweight five-axis parallel machining robot with attitude coupling motion and uniform driving axes’ dynamic response was developed.The optimal design, motion control, and precision guarantee were carried out to realize the high-efficiency and high-quality machining of complex curved parts.Finally, the application verification in AVIC (Aviation Industry Corporation of China) Chengdu Aircraft Industrial (Group) Co., Ltd.was conducted.